2018
DOI: 10.1007/s00705-018-3755-4
|View full text |Cite
|
Sign up to set email alerts
|

Isobavachalcone inhibits post-entry stages of the porcine reproductive and respiratory syndrome virus life cycle

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) is a pathogen of great economic significance that impacts the swine industry globally. Since the first report of a porcine reproductive and respiratory syndrome (PRRS) outbreak, tremendous efforts to control this disease, including various national policies and plans incorporating the use of multiple modified live-virus vaccines, have been made. However, PRRSV is still a significant threat to the swine industry, and new variants continually emerge as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…This pattern indicated that IBC inhibits PRV during the late stage of the viral lifecycle. In addition, these results demonstrated that the mechanisms by which IBC inhibits PRV and PRRSV may differ because IBC inhibited PRRSV at an early stage in our previous study [9]. PRV can induce cell-to-cell fusion, a very important step in viral spreading, at a late stage in the lifecycle.…”
supporting
confidence: 48%
See 1 more Smart Citation
“…This pattern indicated that IBC inhibits PRV during the late stage of the viral lifecycle. In addition, these results demonstrated that the mechanisms by which IBC inhibits PRV and PRRSV may differ because IBC inhibited PRRSV at an early stage in our previous study [9]. PRV can induce cell-to-cell fusion, a very important step in viral spreading, at a late stage in the lifecycle.…”
supporting
confidence: 48%
“…IBC was first isolated from Psoralea corylifolia in 1968 and possesses a broad spectrum of biological activities [8]. In a recent study, IBC also exhibited anti-porcine reproductive and respiratory syndrome virus (PRRSV) activity during the early stage of viral RNA synthesis [9]. To explore whether IBC has anti-PRV activity, we first evaluated the cytotoxicity of IBC on PK15 cells with a Cell Counting Kit-8 (CCK8, Dojindo Laboratories, Japan) according to the manufacturer's instructions.…”
mentioning
confidence: 99%
“…The PRRSV life cycle can be divided into 4 basic stages: attachment, entry, replication and release [53, 54]. Our results showed that xanthohumol significantly inhibited PRRSV adsorption and entry in Marc-145 cells and PAMs.…”
Section: Discussionmentioning
confidence: 84%
“…e components studied include isoliquiritigenin, licochalcone A, isobavachalcone, echinatin, and kanzonol Y. Isoliquiritigenin and licochalcone A evinced anti-HCV activity [92,93]. Isobavachalcone had potent antiporcine reproductive and respiratory syndrome virus (PRRSV) activity in vitro by inhibiting PRRSV replication at the postentry stage of PRRSV infection [94]. Echinatin and isoliquiritigenin showed strong inhibitory effects on influenza viral strains, H1N1, H9N2, and novel H1N1 [28].…”
Section: Antiviral Activitymentioning
confidence: 99%